Eco-Epidemiology of Chagas disease in an endemic area of Colombia : risk factor estimation, Trypanosoma cruzi characterization and identification of blood-meal sources in bugs (2014)
ABSTRACT: The Sierra Nevada de Santa Marta (SNSM) is a mountainous area in Colombia that is highly endemic toChagas disease. We explored some eco-epidemiological attributes involved in the Chagas disease transmission scenarioin three Indigenous communities. An epidemiological survey was done, where parasite infection in reservoirs and insects,Trypanosoma cruzigenotyping, identification of blood-meal sources in intradomiciliary insects using the high-resolutionmelting technique, and some risk factors were evaluated. The results suggest that several dwelling conditions such asthatched palm roofs and mud walls carried the highest risk of finding intradomiciliaryRhodnius prolixus, which 56.41%were infected withT. cruziand fed with human blood. Moreover,T. cruziIa was the most frequent haplotype found ininsects. These results indicate the existence of a domesticT. cruzitransmission cycle that does not overlap with thesylvatic cycle, and highlight the need for efficient entomological control focused to this area.